2015
DOI: 10.1002/uog.14644
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal growth is constrained below optimal for perinatal survival

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 30 publications
7
118
0
2
Order By: Relevance
“…There is a rise in the incidence of stillbirth and perinatal mortality with reducing birthweight centiles, even in those with birthweight centile above the 80th [26,71,72]. This fact is consistent with our recent observation of increasing the proportion of low CPR with reducing birthweight centiles, even in those above the 10 th centile (Figure 1) [73].…”
Section: A Model Of Fetal Surveillancesupporting
confidence: 90%
See 1 more Smart Citation
“…There is a rise in the incidence of stillbirth and perinatal mortality with reducing birthweight centiles, even in those with birthweight centile above the 80th [26,71,72]. This fact is consistent with our recent observation of increasing the proportion of low CPR with reducing birthweight centiles, even in those above the 10 th centile (Figure 1) [73].…”
Section: A Model Of Fetal Surveillancesupporting
confidence: 90%
“…Indeed the majority of stillbirths at term occur in AGA fetuses [25][26][27]. A population based cohort study using data from the medical birth registry of Norway, which included 1.9 million singleton births at or beyond 37 weeks' gestation, showed that the proportion of stillbirths whose weight lies above the 10 th centile (i.e.…”
Section: Assessment Of Fetal Growth At Termmentioning
confidence: 99%
“…A wider range including second-trimester measures could have allowed higher detection, as suggested by another study [12]. We also admit that placental insufficiency may be present in normally growing fetuses [40] but so far there is no consensus on how to define FGR to capture these cases. Finally, we used conditional centiles for longitudinal assessment (that with only two measurements is largely equivalent to growth velocity), but a more complex approach as the one proposed by Deter et al [41] would have resulted in a better performance.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study has shown how the incidence of perinatal death is highest in those with a birth weight below the 2.3 rd centile, falling gradually with an increasing birth weight up to the 80 th and 90 th centiles, at which the lowest death rates occur [7]. …”
Section: Introductionmentioning
confidence: 99%